Ruminal fermentation, nutrients digestibility, and nitrogen balance in lambs fed diet containing high concentrate and essential oil concentrations of lemon grass (Cymbopogon citratus) (Acta Scientiarum. Animal Sciences, 2025)
This experiment evaluated the effects of doses of essential oil of lemon grass (Cymbopogon citratus) in rumen fermentation, nutrients digestibility and nitrogen balance in lambs. The treatments: negative control/CTL (no additives); positive control/MON (addition of 25 ppm of monensin Kg- of dry matter); and 1.25, 2.5 and 3.75 mL essential oil Kg of diet as feed. Twenty-five crossbreed Dorper x Santa Ines lambs with 45.6 ± 10.7 Kg of body weight and cannulated in the rumen allocated into randomized complete blocks design with five replicates per treatment. It was possible to verify that all the treatments began to alter some parameters of the ruminal fermentation of the diet offering. Essential oil of lemon grass used had similar results to monensin on parameters of ruminal, on day 21 compared with day zero, essential oil presented high concentrations of ammoniacal nitrogen in the rumen, indicating that there was protein degradation greater than monensin. Not verified effect of essential oil in nutrient intake and nitrogen retained, even though there was improvement in the digestibility of dry matter and crude protein, and these effects were similar to monensin. During the 21 days, essential oil evaluated is effective manipulating some parameters of the ruminal fermentation.